Forage yield and morphogenesis of Megathyrsus maximus cultivars in Roraimas’s savannas (Research, Society and Development, 2020)
In order to evaluate the forage productivity and the morphogenic and structural characteristics of Megathyrsus maximus cultivars (Massai, Mombasa, Kenya, Tamani, Tanzania and Zuri), an experiment was conduct under natural environmental conditions in the savannahs of Roraima. The highest yields of green dry matter (GDM) were found with cultivars Zuri (4,317 kg ha-1) and Mombasa (4,115 kg ha-1), followed by Kenya (3,868 kg ha-1) and Tamani (3,755 kg ha-1), while Massai (3,341 kg ha-1) and Tanzania (3,225 kg ha-1) were the least productive. GDM yield was directly correlated with LAI and inversely proportional to tiller population density (TPD). The cultivars Tanzania and Kenya had the highest number of tiller leaves and leaf appearance rates, while the highest leaf expansion rates were estimate in cultivars Zuri and Kenya. The highest average length of tiller leaves was estimate in the cultivars Zuri and Mombasa. Leaf senescence rates were inversely proportional to TPD and the highest recorded with the cultivars Mombasa and Tamani. The six cultivars of M. maximus showed satisfactory forage yields and can be recommend for cultivation in the edaphoclimatic conditions of the of Roraima’s savannas. The determination of morphogenic and structural characteristics can contribute to the establishment of appropriate and specific management practices for each cultivar, aiming to optimize its productivity and reduce losses due to leaf senescence.